Letter - Sullivan, Bernard
026-0040-001 National Union of Tailors and Garment Workers Incorporating the Amalgimated Society of Tailors and Tailoresses, the Scottish Operative Tailors and Tailoresses' Association and the Garment Workers' Union Affiliated to the British, Scottish and Irish Trades Union Congresses, Labour Party, International Clothing Workers' Federation, &c. LONDON No. 1 BRANCH ALL COMMUNICATION TO BE ADDRESSED TO:- BERNARD SULLIVAN SECRETARY YOUR REF. OUR REF. BS/EP. OFFICE: 194/200, BISHOPSGATE, E.C. 2 TELEPHONE BISHOPSGATE 1930 10th August, 1939. Mr. Tewson, Assistant Secretary, Trades Union Congress, Transport House, Smith Square, S.W.1. Dear Mr. Tewson, Accept I have an offer of 200 Sports Coats, Flannel Trousers at 10/6d. per suit for Ben Williams, Bow Road, E. They are a bargain and I recommend their acceptance. All to Rouen Will you also advise me of where to send Polikoffs parcels. You thought they would be more suitable for Refugees in England. Yours sincerely, Bernard Sullivan L.C.C. London Central (No.1.) Branch Secretary. 292/946/26/40